2010
DOI: 10.1055/s-0030-1254164
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Congenital Chylothorax in Children

Abstract: The initial postnatal medical management of CC should consist of thoracocentesis, drainage by tube thoracostomy, and total parenteral nutrition. If this treatment fails after 10 days, we propose using alternative therapies such as somatostatin (although its efficacy is not clear) and surgery. Chemical pleurodesis by intrapleural injection of povidone-iodine must be avoided in infants and small babies. Surgical management by pleural abrasion and/or pleurectomy appears to be safe and effective. Early surgical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
20

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
0
7
0
20
Order By: Relevance
“…Surgical management with pleural abrasion and pleurectomy has been advocated by some centres to be an effective alternative for large, refractory effusions. 18 An algorithm for management of chylothorax based on the experience in our centre is proposed (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management with pleural abrasion and pleurectomy has been advocated by some centres to be an effective alternative for large, refractory effusions. 18 An algorithm for management of chylothorax based on the experience in our centre is proposed (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors advocate for early thoracic duct ligation or pleurodesis in patients failing conservative medical treatment. (16-18) It is not yet possible to identify the subset of patients who will drain for long times and consequently be at risk for protein malnutrition, electrolyte, and immunologic abnormalities. We believe that spontaneous resolution of chylothorax is unlikely when initial drainage volume is excessive.…”
Section: Commentmentioning
confidence: 99%
“…The right thoracotomy is the most easy and efficient incision to ligate the thoracic duct when the patient has no situs inversus [8]. Some authors have shown the benefit of prophylactic mass ligation of the thoracic duct in patients who underwent oesophagectomy and pulmonary resection [9]. However, the interest of the prophylactic ligation has not been verified in children with congenital cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%